THE INFLUENCE OF USE OF PODCAST LEARNING MEDIA ON LISTING SKILLS - Hanum, Linda Laela; Gunawan, Agus; Prapramdana, Gilang Krispsiyadi (Journal Of Educational Experts (JEE), 2023)
This research is a study of students' listening skills in the Indonesian language content of the Legend of Putri Niwer Gading which is still very low. The purpose of this study was to find out the differences in the results of listening skills (posttest) for students who used the Podcast learning media and students who used the Strip Story learning media for class V SDN 1 Awirarangan. This research method used quasi-experimental with a posttest-pretest control group research design, with research subjects consisting of 21 students in class VA as the control class, while class VC as the experimental class with 23 students. The instrument used in this study was a written test in the form of an essay. Data analysis was used in the experimental class and control class manually using the t test formula and the n-goin test formula. This is shown from the results of the t test analysis that the tcount is greater than ttable and n-gain test which shows an increase in the moderate category. So thus, the conclusion of this study can be stated that there are differences in students' listening skills between classes using Podcast learning media and classes using Strip Story Learning Media and there is an increase in students' listening skills between classes using Podcast learning media and classes using learning media Strip Story in class V SDN 1 Awirarangan